Analisis Motivasi Belajar Siswa Menggunakan Video Pembelajaran Sistem Daring Pada Pelajaran IPA Kelas V SDN 1 Selabintana Kota Sukabumi - Adinda Rahayu; Din Azwar Uswatun; Astri Sutisnawati (Universitas Negeri Makassar, 2021)
This study aims to describe the motivation for learning science in class V by using online-based learning videos during the covid-19 pandemic at SDN 1 Selabintana, Sukabumi City. The type of research used in this research is descriptive qualitative. The instrument used was a learning motivation questionnaire, which consisted of 15 statement items. The results showed that students' learning motivation with learning videos obtained an average percentage of 82.27% with high motivation criteria. The results of motivation to learn science using learning videos based on indicators are obtained as follows: indicators of the desire to succeed in the category of high motivation with a percentage of 86%; The existence of encouragement and need in learning is in the category of high motivation with a percentage of 81.5%; The existence of hopes and aspirations for the future is in the category of high motivation with a percentage of 82%; The existence of appreciation in learning is categorized as moderate motivation with a percentage of 79.50%; The existence of interesting activities in learning is categorized as high motivation with a percentage of 82.33%